2017
DOI: 10.1556/1886.2017.00009
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblasts: the unknown sentinels eliciting immune responses against microorganisms

Abstract: Fibroblasts are present in all tissues but predominantly in connective tissues. Some of their functions include contractility, locomotion, collagen and elastin fiber production, and the regulation and degradation of the extracellular matrix. Also, fibroblasts act as sentinels to produce inflammatory mediators in response to several microorganisms. There is evidence that fibroblasts can synthesize toll-like receptors (TLRs), antimicrobial peptides, proinflammatory cytokines, chemokines, and growth factors, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(66 citation statements)
references
References 45 publications
0
65
0
1
Order By: Relevance
“…These balancing events may however produce overshoots, manifested by sustained and unwanted fibroblast activity and chronic inflammation in affected tissue. The fibroblast‐immune crosstalk has been the focus of other reviews and will only be discussed here with respect to novel approaches aimed to dissect the rate limiting functions of fibroblasts on innate and adaptive immune reactions.…”
Section: Evolution Of the Immune Regulatory Functions Of Fibroblastsmentioning
confidence: 99%
See 1 more Smart Citation
“…These balancing events may however produce overshoots, manifested by sustained and unwanted fibroblast activity and chronic inflammation in affected tissue. The fibroblast‐immune crosstalk has been the focus of other reviews and will only be discussed here with respect to novel approaches aimed to dissect the rate limiting functions of fibroblasts on innate and adaptive immune reactions.…”
Section: Evolution Of the Immune Regulatory Functions Of Fibroblastsmentioning
confidence: 99%
“…Beyond the secretome, fibroblasts also engage the immune system through their expression of TLRs (toll‐like receptors) and production of antimicrobials such as defensins, possibly acting as sentinels in various organs such as the skin and lung (reviewed in ). The expression of TLRs by synovial fibroblasts may also be implicated in the chronic inflammatory responses associated with rheumatoid arthritis .…”
Section: Evolution Of the Immune Regulatory Functions Of Fibroblastsmentioning
confidence: 99%
“…Studies have also shown that CD14 ( [6,25], and this study) as well as TLR2 and TLR4 are expressed on human GFs and, thus, mediate pathogen interactions with GFs. Liu et al (2015) exposed a monocytic cell line to a TLR4 agonist, which enhanced the expression of adherence genes LFA-1 and VLA-4, suggesting that binding of monocytes to fibroblasts is likely partly regulated by LFA-1 and VLA-4 [26,27].…”
Section: The Role Of Monocytes In Tlr Activationmentioning
confidence: 99%
“…Fibroblasts can themselves respond to both bacterial and viral infection as they express numerous PRRs, such as the Toll-like receptors. 42 Thus, fibroblasts can be activated either as a result of infection or in response to PAMPs such as LPS, poly(I:C) and flagellin. A common response to such innate stimuli is the release of soluble factors such as the potent neutrophil chemotactic factors CXCL8, as well as CXCL10 and CCL2, demonstrating a general ability to recruit innate responder cells in response to stimulation.…”
Section: Fibroblast Innate Immunological Functionsmentioning
confidence: 99%